The Role of Contact X-Ray Brachytherapy in Early Rectal Cancer – Who, when and How?. Issue 2 (February 2023) - Sun Myint, A.; Dhadda, A.; Stewart, A.; Mills, J.; Sripadam, R.; Rao, C.; Hunter, A.; Hershman, M.; Franklin, A.; Chadwick, E.; Banerjee, A.; Rockall, T.; et al.
Abstract: The National Institute for Health and Care Excellence (NICE) has recommended the use of contact X-ray brachytherapy (CXB) for rectal cancer patients who are not suitable for surgery. At present, patients with early rectal cancer who wish to avoid major surgery and a stoma are not usually offered CXB as an alternative treatment option to surgery. The main reason for this has been a lack of large, randomised trial evidence, hence NICE encouraged provision of this evidence in their recommendation. In 2015, the OPERA (Organ Preservation in Early rectal Adenocarcinoma) trial was set up and the 3-year organ-preservation results were presented at the American Society of Clinical Oncology (ASCO) meeting in Chicago on 4 June 2022. We are now awaiting full publication of the OPERA results. Most rectal cancer patients who are not suitable for surgery are currently offered external beam radiotherapy (EBRT) with or without chemotherapy after the multidisciplinary discussions. Clinical complete response (cCR) rates vary between 20 and 50% after EBRT. Those who achieve cCR usually adopt a 'watch and wait' policy, but patients who have residual disease are often not offered any additional treatment. We hypothesised that dose escalation with a CXB boost could achieve a higher cCR and therefore lead to improved organ-preservation rates. This was the rationale behind the OPERA trial, which randomised patients between standard of care [EBRT with chemotherapy (EBCRT)] followed by an EBRT boost against EBCRT with a CXB boost to evaluate the role of CXB in dose escalation. In 1993, the first CXB centre was established in the UK at Clatterbridge Cancer Centre. There are now four centres offering CXB in the UK and 10 centres in Europe. Patients should be provided with full information during the consent discussion and offered all the treatment options that are available, so that they can share in decision making and be empowered to make treatment decisions of their choice after proper fully informed consent. Randomised trial evidence of the role of dose escalation with CXB from the OPERA trial, when published, will help in consenting patients who are keen to avoid surgery. We hope this review will help to provide some information about who should be offered CXB, when this modality should be offered and how this is delivered.